Participation of gut microbiota and bacterial translocation in chronic systemic inflammation in recently diagnosed rheumatoid arthritis patients - Catherine Dunyach-Remy; Cassandra Pouget; Yves-Marie Pers; Cécile Gaujoux-Viala; Christophe Demattei; Florian Salipante; Lucia Grenga; Jean Armengaud; Jean-Philippe Lavigne; Christian Jorgensen (Current Research in Microbial Sciences)
The objective of this study was to investigate the link between gut microbiota (GM) dysbiosis, gut inflammation, and bacterial translocation (BT) in recently diagnosed rheumatoid arthritis (RA). This case-control, observational study prospectively recruited recently diagnosed (<12 months) RA patients and age-matched healthy controls (HC) from two French hospitals between July 2014 to March 2018. The primary objective was to investigate GM composition in each group using 16S rRNA sequencing and metaproteomics approaches. Three plasmatic BT markers (sCD14, LPS-binding protein, and number of 16S rRNA gene copies) and one intestinal permeability marker (I-FABP) were quantified in blood samples.Twenty-five were included in each group, and 50 stools and blood samples were analyzed. 16S rRNA gene analysis showed an decrease in Coprococcus in RA patients after Body Mass Index and HLA status. Circulating bacterial DNA (number of copies of the 16S rRNA gene) and plasmatic I-FABP were higher in RA patients compared to HCs (p < 0.01), indicating increased BT and intestinal permeability in these patients. Metaproteomics from stool samples highlighted an increased host humoral immune response in RA, with elevated levels of inflammatory proteins (azurocidin, cathepsin G, neutrophil defensing 1). Gut inflammation may contribute to increased intestinal permeability, leading to BT into the systemic circulation and thus chronic inflammation.